A composite active aluminum-based ozone oxidation catalyst and its preparation method and application

By using β-Al2O3-configured aluminum-based support to support carbon and transition metals in ozone catalytic oxidizer, the problem of insufficient decomposition capacity of alumina support to O3 and easy wear of activated carbon is solved, and efficient ozone oxidation catalysis is achieved, which significantly improves the catalyst structural stability and catalytic degradation rate.

CN118847116BActive Publication Date: 2024-12-24SUZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411340066.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-24
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

The structural stability and catalytic efficiency of existing ozone catalytic oxidants are defective, especially the alumina support lacks the ability to decompose O3 and the organic matter transfer efficiency, and the activated carbon is prone to wear and leads to wastewater pollution.

Method used

The aluminum-based support with a β-Al2O3 configuration is loaded with a small amount of carbon and transition metal elements, and a composite activated aluminum-based ozone oxidation catalyst is prepared by spray-drying granulation and calcining to optimize the surface properties and structural stability of the catalyst.

Benefits of technology

The catalytic activity is significantly improved under low carbon and low transition metal content, the mass transfer efficiency and structural stability of the catalyst are enhanced, and the wastewater toxicity and turbidity problems caused by carbon particles are avoided, and the catalytic degradation rate is increased by nearly 70%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118847116B_ABST
    Figure CN118847116B_ABST
Patent Text Reader

Abstract

The present invention discloses a composite active aluminum-based ozone oxidation catalyst and a preparation method and application thereof, wherein the catalyst comprises an aluminum-based carrier and a transition metal element and carbon loaded on the aluminum-based carrier, wherein the aluminum-based carrier is an aluminum-based carrier of β-Al2O3 configuration, and the mass percentage of carbon in the catalyst is 0.1-1wt%. The composite active aluminum-based ozone oxidation catalyst is obtained by spray drying and calcining a precursor liquid containing an aluminum source, a carbon source, a transition metal source and a salt template agent. Compared with other aluminum-based carriers, the catalyst formed by using an aluminum-based material with β-Al2O3 configuration as a carrier exhibits high catalytic activity for ozone catalytic oxidation under low carbon content and low transition metal content.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, and in particular to a composite active aluminum-based ozone oxidation catalyst and a preparation method and application thereof. Background Art

[0002] In the process of ozone catalytic oxidation, the structural stability and surface properties of the catalyst are crucial for the generation of free radicals. Studies have shown that using materials such as alumina and activated carbon as carriers to load metal sites has been proven to be an effective and practical method. Porous alumina is very suitable for fixing transition metals such as Fe, Cu, Mo, Mn and Co due to its large specific surface area and relatively excellent mechanical stability. However, it is worth noting that alumina, as a non-p-type semiconductor, lacks sufficient holes and is limited in its ability to electrophilically adsorb O3 or -OH, thus having a relatively small effect on promoting the decomposition of O3. In addition, alumina has a weak affinity for aromatics, which restricts the mass transfer efficiency of organic matter from the aqueous phase to the catalyst surface, which has become the rate-limiting step in the degradation of organic matter by ozone catalytic oxidation. Although it is challenging to seek efficient and scalable methods to optimize alumina carriers and improve their surface properties, it is of great significance.

[0003] Block activated carbon, which not only has a high surface area but also is rich in various functional groups on its surface, has been shown to be an ideal carrier for loading metals and effectively catalyzing ozone decomposition. These oxygen-containing functional groups can act as initiators of OH in free radical chain reactions and can also serve as adsorption sites for organic matter, thereby accelerating the mass transfer process. However, due to the amorphous and loose structure of activated carbon, these catalysts are easily worn and detached during the gas / liquid friction process. In addition, the detached carbon particles enter the water phase together with the loaded metals, which will lead to increased toxicity and turbidity of the wastewater.

[0004] Due to the defects of the current ozone catalysts using materials such as alumina and activated carbon as carriers in terms of catalytic efficiency and structural stability, there is an urgent need for an ozone oxidation catalyst that has both good structural stability and catalytic efficiency. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a composite active aluminum-based ozone oxidation catalyst and a preparation method and application thereof. The composite active aluminum-based ozone oxidation catalyst comprises an aluminum-based carrier with a β-Al2O3 configuration and a small amount of carbon elements and transition metal elements loaded on the aluminum-based carrier. The composite active aluminum-based ozone oxidation catalyst can be obtained by spray drying, granulation and calcination of a precursor source containing each element in the presence of potassium salt and / or sodium salt. The preparation method is simple and easy to control, and is suitable for industrial production. Moreover, the composite active aluminum-based ozone oxidation catalyst exhibits excellent catalytic performance under the conditions of low carbon content and low transition metal element content.

[0006] Specifically, the present invention provides the following technical solutions:

[0007] The first aspect of the present invention provides a composite active aluminum-based ozone oxidation catalyst, which comprises an aluminum-based carrier and a transition metal element and carbon loaded on the aluminum-based carrier, wherein the aluminum-based carrier is an aluminum-based carrier with a β-Al2O3 configuration; the transition metal element comprises one or more of Fe, Cu, Mo, Mn and Co; and the mass percentage of carbon in the composite active aluminum-based ozone oxidation catalyst is 0.1wt%-1wt%.

[0008] Furthermore, the aluminum-based carrier is preferably K-type β-Al2O3 and / or Na-type β-Al2O3.

[0009] Furthermore, the mass percentage of transition metal elements in the composite active aluminum-based ozone oxidation catalyst is preferably 1wt%-4wt%.

[0010] Furthermore, the specific surface area of ​​the composite active aluminum-based ozone oxidation catalyst is preferably 4-20 m 2 / g.

[0011] Furthermore, the composite active aluminum-based ozone oxidation catalyst further comprises nitrogen supported on the aluminum-based carrier, and the mass percentage of nitrogen in the composite active aluminum-based ozone oxidation catalyst is preferably 0-0.5wt%.

[0012] The second aspect of the present invention provides a method for preparing the composite active aluminum-based ozone oxidation catalyst according to the first aspect, comprising the following steps:

[0013] (1) dissolving an aluminum source, a transition metal source, a carbon source and a salt template in water to obtain a uniformly mixed precursor solution; the salt template is a potassium salt and / or a sodium salt;

[0014] (2) spray drying the precursor solution prepared in step (1) to obtain microsphere powder, and then calcining the microsphere powder to obtain the composite active aluminum-based ozone oxidation catalyst.

[0015] Furthermore, in step (1), the aluminum source includes but is not limited to ammonium aluminum sulfate; the transition metal source includes a copper source, and the copper source is preferably copper nitrate and / or its hydrate; the carbon source can be selected from one or more of glucosamine and its salts, glycine, glucose and sucrose; and the salt template is preferably potassium chloride and / or sodium chloride.

[0016] Furthermore, in step (1), the total solid content of the precursor solution is preferably 6 wt%-14 wt%.

[0017] Furthermore, in step (1), the mass ratio of the aluminum source to the salt template is preferably 1:(1-6), more preferably 1:(3-5).

[0018] Furthermore, in step (2), during the spray drying process: the pressure is preferably 0.1-0.5 kg / cm 2 The working vibration frequency of the atomizer is preferably 5-15kHz, the amplitude is preferably 10-20Vpp, the hot air flow rate is preferably 250-350L / min, and the tower top temperature is preferably 150-200℃.

[0019] Furthermore, in step (2), the particle size of the microsphere powder is preferably 80-90 μm.

[0020] Furthermore, in step (2), the calcination treatment is carried out under an inert atmosphere, and the inert atmosphere is argon and / or nitrogen.

[0021] Furthermore, in step (2), the calcination temperature is preferably 600-800°C, and the calcination time is preferably 1-4h; more preferably, during the calcination process: the temperature is increased from room temperature to the calcination temperature at a heating rate of 2-5°C / min.

[0022] Furthermore, the preparation method also includes the steps of washing and drying the calcined product to remove residual salt template.

[0023] The third aspect of the present invention provides an application of the composite active aluminum-based ozone oxidation catalyst described in the first aspect or the composite active aluminum-based ozone oxidation catalyst prepared by the preparation method described in the second aspect in wastewater treatment; the types of pollutants contained in the wastewater include but are not limited to sodium oxalate.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The present invention provides a composite active aluminum-based ozone oxidation catalyst, which is obtained by loading a small amount of carbon, transition metal elements, etc. on an aluminum-based carrier of β-Al2O3 configuration. Compared with the catalyst prepared by loading a relatively high content of carbon and transition metal elements on a γ-Al2O3 aluminum-based carrier, the catalyst prepared by using β-Al2O3 as an aluminum-based carrier in the present invention exhibits better catalytic activity under the conditions of low specific surface area, low carbon content and low transition metal element content, which provides a new idea for the selection of carriers for high-activity catalysts and is conducive to reducing the preparation cost of catalysts.

[0026] 2. The composite active aluminum-based ozone oxidation catalyst provided by the present invention has a low carbon content, which makes the catalyst have high catalytic activity while improving the structural stability of the catalyst, and can effectively avoid the problems of excessive carbon content, easy shedding of carbon particles, decreased catalytic performance, increased wastewater toxicity, and turbidity. Specifically, the present invention introduces residual carbon into the catalyst, which has at least the following advantages: (1) optimizes the surface properties of the aluminum-based carrier and enhances the mass transfer efficiency; (2) the introduction of residual carbon can promote the Cu + and Cu 2+ The electron transfer between Cu 2+ Reduction to Cu + , so that there is more Cu + As an active site, it donates electrons to ozone, catalyzing the decomposition of ozone to produce active free radicals; (3) The introduced residual carbon has the activity of catalyzing the decomposition of ozone, which can further increase the active sites of the catalyst.

[0027] 3. The present invention also provides a method for preparing the above-mentioned composite active aluminum-based ozone oxidation catalyst, which is obtained by spray drying, granulation and calcination of a precursor source containing aluminum, carbon and transition metal elements in the presence of potassium salt and / or sodium salt. The preparation method is simple and easy to control. The preparation of a composite active aluminum-based ozone oxidation catalyst with uniform particle size and performance can be achieved by controlling the spray drying process parameters and the calcination process parameters, and the catalyst is suitable for industrial production.

[0028] 4. The composite active aluminum-based ozone oxidation catalyst provided by the present invention is used to catalyze ozone oxidation treatment of wastewater (for example, wastewater containing sodium oxalate), showing excellent catalytic performance, which is significantly better than commercial catalysts (4wt% CuO / γ-Al2O3), and the degradation rate of catalytic degradation for 25 minutes is increased by nearly 70%; and the catalyst prepared by the present invention comprising an aluminum-based carrier with a β-Al2O3 configuration, compared with the catalyst comprising an aluminum-based carrier with a γ-Al2O3 configuration, shows better catalytic activity at a lower carbon loading, copper loading and specific surface area. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a SEM image of the composite active aluminum-based catalyst prepared in Example 1 of the present invention, wherein the scale of a1 is 2 μm, and the scale of a2 is 500 nm;

[0030] Figure 2 This is the XRD pattern of the composite active aluminum-based catalyst prepared in Example 1 of the present invention;

[0031] Figure 3 This is a SEM image of the composite active aluminum-based catalyst prepared in Comparative Example 1 of the present invention, with a scale of 2 μm;

[0032] Figure 4This is the XRD diagram of the composite active aluminum-based catalyst prepared in Comparative Example 1 of the present invention;

[0033] Figure 5 This is the XRD diagram of the composite active aluminum-based catalyst prepared in Comparative Example 2 of the present invention;

[0034] Figure 6 The test results of the composite active aluminum-based catalyst prepared in Example 1 and Comparative Examples 1 and 2 of the present invention and the commercial catalyst 4wt% CuO / γ-Al2O3 catalyzing the ozone oxidation of sodium oxalate;

[0035] Figure 7 These are the metal valence content analysis results of the composite active aluminum-based catalysts prepared in Example 1 and Comparative Example 1 of the present invention (obtained by testing using a Thermo Fisher ESCALAB 250Xi spectrometer). DETAILED DESCRIPTION

[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are for the purpose of describing specific embodiments only and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items. The term "includes" or "comprising" described in the present invention means that it may include or contain other components in addition to the components described. The term "includes" or "comprising" described in the present invention may also be replaced by the closed form "for" or "consisting of..."

[0037] The embodiments of the present invention provide a composite active aluminum-based ozone oxidation catalyst, comprising an aluminum-based carrier and a transition metal element and carbon loaded on the aluminum-based carrier, wherein the aluminum-based carrier is an aluminum-based carrier with a β-Al2O3 configuration; the transition metal element comprises one or more of Fe, Cu, Mo, Mn and Co; and the mass percentage of carbon in the composite active aluminum-based ozone oxidation catalyst is 0.1wt%-1wt%.

[0038] In the present invention, the aluminum-based carrier is preferably a K-type β-Al2O3 and / or a Na-type β-Al2O3 aluminum-based carrier, wherein the K-type β-Al2O3 is an aluminum-based carrier containing the K element and having a β-Al2O3 configuration, and the Na-type β-Al2O3 is an aluminum-based carrier containing the Na element and having a β-Al2O3 configuration.

[0039] In the present invention, residual carbon is introduced into the catalyst to improve the catalytic activity of the catalyst, and the amount of carbon doping is controlled to ensure that the catalyst has high catalytic activity and good structural stability. Preferably, the mass percentage of carbon in the catalyst is controlled in the range of 0.1wt%-1wt%, for example, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, etc., including but not limited to the values ​​listed above.

[0040] In the present invention, the mass percentage of transition metal elements in the composite active aluminum-based ozone oxidation catalyst is preferably 1wt%-4wt%, for example, 1wt%, 1.12wt%, 1.5wt%, 2.1wt%, 2.5wt%, 2.8wt%, 3wt%, 4wt%, etc., including but not limited to the values ​​listed above.

[0041] In the present invention, the specific surface area of ​​the composite active aluminum-based ozone oxidation catalyst is preferably 4-20 m 2 / g, for example 4m 2 / g, 6m 2 / g, 8m 2 / g, 10m 2 / g, 12m 2 / g, 14m 2 / g, 16m 2 / g, 18m 2 / g, 20m 2 / g, etc., including but not limited to the values ​​listed above. The composite active aluminum-based ozone oxidation catalyst provided by the present invention exhibits higher catalytic activity under low specific surface area conditions compared to aluminum-based ozone oxidation catalysts with high specific surface area.

[0042] In some preferred embodiments of the present invention, the composite active aluminum-based ozone oxidation catalyst also includes nitrogen loaded on an aluminum-based carrier to further improve the catalytic performance of the catalyst; wherein the mass percentage of nitrogen in the composite active aluminum-based ozone oxidation catalyst is 0-0.5wt%, for example, 0.04wt%, 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, 0.35wt%, 0.4wt%, 0.5wt%, etc., including but not limited to the values ​​listed above.

[0043] The present invention also provides a method for preparing the composite active aluminum-based ozone oxidation catalyst, comprising the following steps:

[0044] (1) dissolving an aluminum source, a transition metal source, a carbon source and a salt template in water to obtain a uniformly mixed precursor solution; the salt template is a potassium salt and / or a sodium salt;

[0045] (2) spray drying the precursor solution prepared in step (1) to obtain microsphere powder, and then calcining the microsphere powder to obtain the composite active aluminum-based ozone oxidation catalyst.

[0046] In the present invention, the aluminum source in step (1) includes but is not limited to ammonium aluminum sulfate. The aluminum source that can form a β-Al2O3-structured aluminum-based carrier by the above-mentioned preparation method is within the protection scope of the present invention.

[0047] In the present invention, the transition metal source in step (1) includes a copper source, preferably copper nitrate and / or its hydrate, including but not limited to the copper sources listed above.

[0048] In the present invention, the carbon source in step (1) can be selected from one or more of glucosamine and its salts, glycine, glucose and sucrose.

[0049] In the present invention, the salt template in step (1) is preferably potassium chloride and / or sodium chloride, which can be easily removed by washing with water. In the preparation method provided by the present invention, the use of the salt template allows the precursor liquid to be spray-dried and granulated by the assembly of the aluminum source and the salt template in the droplets and the removal of the salt template, thereby forming a catalyst with a multi-level pore structure and increasing the specific surface area of ​​the catalyst to a certain extent; in addition, the potassium and sodium ions in the salt template can participate in the formation of the aluminum-based carrier, thereby forming a K-type or Na-type β-Al2O3 with a specific morphology.

[0050] In the present invention, the total solid content of the precursor solution in step (1) is preferably 6-14wt%, such as 6wt%, 8wt%, 10wt%, 12wt%, 14wt%, etc., including but not limited to the values ​​listed above.

[0051] In the present invention, the mass ratio of the aluminum source to the salt template in step (1) is preferably 1: (1-6), such as 1: 1, 1: 2, 1: 3, 1: 4, 1: 5, 1: 6, etc., including but not limited to the mass ratios listed above. In the preparation method provided by the present invention, if the content of the salt template is too little, the residual carbon content and the copper content in the prepared catalyst are too low, and the catalytic performance is poor. If the content of the salt template is too high, the catalyst performance is not significantly improved, resulting in a waste of resources. Therefore, preferably, the mass ratio of the aluminum source to the salt template is controlled at 1: (1-6), more preferably 1: (3-5).

[0052] In the present invention, the spray drying in step (2) is specifically as follows: the precursor solution in the material tank is broken into uniform small droplets by compressed air through a microfluidic aerosol nozzle, and then enters a drying tower to fully contact with hot air, and the water evaporates rapidly to form microsphere powder; in the above-mentioned spray drying process: the pressure is preferably 0.1-0.5 kg / cm 2The working vibration frequency of the atomizer is preferably 5-15kHz, the amplitude is preferably 10-20Vpp, the hot air flow rate is preferably 250-350L / min, and the tower top temperature is preferably 150-200°C; in some preferred embodiments, the pressure during the spray drying process is 0.3kg / cm 2 , the working vibration frequency of the atomizer is 10kHz, the amplitude is 15Vpp, the hot air flow rate is 300L / min, and the tower top temperature is 170℃.

[0053] In the present invention, the particle size of the microsphere powder can be controlled by adjusting the nozzle size and wind speed used in the spray drying process; in some preferred embodiments, the particle size of the microsphere powder obtained by spray drying is preferably 80-90 μm.

[0054] In the present invention, the calcination treatment in step (2) is preferably carried out under an inert atmosphere, wherein the inert atmosphere is argon and / or nitrogen.

[0055] In the present invention, the calcination treatment in step (2) is specifically: heating from room temperature to the calcination treatment temperature at a heating rate of 2-5°C / min, the calcination treatment temperature is preferably 600-800°C, for example 600°C, 650°C, 700°C, 750°C, 800°C, etc., and the calcination treatment time is preferably 1-4h, for example 1h, 2h, 3h, 4h, etc.

[0056] In the present invention, the preparation method further comprises the steps of washing and drying the calcined product to remove residual salt template; wherein the washing method comprises: immersing the calcined product in water and oscillating at a constant temperature.

[0057] The embodiments of the present invention also provide an application of a composite active aluminum-based ozone oxidation catalyst in wastewater treatment; in some preferred embodiments, the composite active aluminum-based ozone oxidation catalyst is used to treat wastewater containing sodium oxalate, and exhibits excellent catalytic activity.

[0058] The present invention is further described below in conjunction with specific embodiments and drawings so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0059] Example 1

[0060] This embodiment relates to the preparation of a composite active aluminum-based ozone oxidation catalyst, which is specifically as follows:

[0061] (1) Weigh 5 g of ammonium aluminum sulfate, 20 g of potassium chloride, 1.6875 g of glucosamine hydrochloride and 0.2055 g of copper nitrate trihydrate into an ultrapure aqueous solution and stir at room temperature for 3 h. The total solid content of the precursor solution is 12 wt %.

[0062] (2) Pour the above precursor solution into a polytetrafluoroethylene material tank, use compressed air to break the precursor solution in the material tank into uniform small droplets through a microfluidic aerosol nozzle, and spray dry the precursor solution under the conditions of a tower top temperature of 170°C and a hot air flow rate of 300L / min. The collected dry powder is placed in a corundum ark and then placed in a tube furnace for calcination. It is heated to a corresponding temperature of 750°C at a heating rate of 5°C / min under an argon atmosphere and maintained for 2 hours. After that, the calcined sample is immersed in a glass container containing ultrapure water, placed in a constant temperature oscillator for oscillation for 3 hours, then vacuum filtered and washed with a certain amount of ultrapure water to completely remove the salt components in the material, and finally vacuum dried overnight at 60°C to obtain a composite active aluminum-based ozone oxidation catalyst.

[0063] The SEM image of the composite active aluminum-based ozone oxidation catalyst prepared in this example is as follows: Figure 1 As shown in the figure, it can be seen that the prepared composite active aluminum-based ozone oxidation catalyst presents a pyramidal morphology. The XRD pattern of the composite active aluminum-based ozone oxidation catalyst is as follows Figure 2 As shown in the figure, it can be seen that the diffraction peak position of the aluminum-based carrier of the composite active aluminum-based ozone oxidation catalyst is consistent with that of K-type β-Al2O3. It can be seen that the aluminum-based carrier in the composite active aluminum-based ozone oxidation catalyst prepared in this embodiment is an aluminum-based carrier with a β-Al2O3 configuration.

[0064] Comparative Example 1

[0065] This comparative example relates to the preparation of a composite active aluminum-based ozone oxidation catalyst, which differs from Example 1 only in that the aluminum source is changed to aluminum sulfate, the amount of glucosamine hydrochloride added is changed to 1.8625 g, and the amount of copper nitrate trihydrate added is changed to 0.2268 g. The remaining operations are consistent with Example 1, and a composite active aluminum-based ozone oxidation catalyst is prepared.

[0066] The SEM image of the composite active aluminum-based ozone oxidation catalyst prepared in this comparative example is as follows Figure 3 As shown in the figure, it can be seen that the prepared composite active aluminum-based ozone oxidation catalyst is a mixed form, most of the particles are pyramidal morphology, the surface is smooth and has no voids, but some particles still have a flake morphology. The XRD pattern of the composite active aluminum-based ozone oxidation catalyst is as follows Figure 4 As shown, the composite active aluminum-based ozone oxidation catalyst contains diffraction peaks belonging to K-type β-Al2O3 and aluminum hydroxide. It can be seen that the aluminum-based carrier of the composite active aluminum-based ozone oxidation catalyst prepared in this comparative example contains β-Al2O3 aluminum-based carrier and aluminum hydroxide.

[0067] Comparative Example 2

[0068] This comparative example relates to the preparation of a composite active aluminum-based ozone oxidation catalyst, which differs from Example 1 only in that the amount of glucosamine hydrochloride added is changed to 5 g, and the calcination method is changed to heating to a corresponding temperature of 750°C at a heating rate of 5°C / min in an argon atmosphere and maintaining for 2 hours, and then heating to a corresponding temperature of 600°C at a heating rate of 5°C / min in an air atmosphere after cooling and maintaining for 3 hours. The remaining operations are consistent with Example 1, and a composite active aluminum-based ozone oxidation catalyst is prepared.

[0069] The XRD pattern of the composite active aluminum-based ozone oxidation catalyst prepared in this comparative example is as follows Figure 5 As shown, the composite active aluminum-based ozone oxidation catalyst contains a diffraction peak belonging to γ-Al2O3, which shows that the aluminum-based carrier of the composite active aluminum-based ozone oxidation catalyst prepared in this comparative example is a γ-Al2O3 aluminum-based carrier.

[0070] Application and performance testing

[0071] The composite active aluminum-based ozone oxidation catalyst prepared in the above examples and comparative examples and the commercial catalyst 4wt% CuO / γ-Al2O3 (wherein 4wt% refers to the content of copper in the catalyst as 4wt%) were used to catalyze ozone oxidation of sodium oxalate. The catalytic ozone oxidation process was carried out in a two-necked flask in a semi-batch mode. The specific method is as follows:

[0072] 150mL of 2mM sodium oxalate solution and 30mg of catalyst were added into the reactor and stirred with a magnetic stirrer. Ozone was prepared by dry high-purity oxygen (30mL / min) through an ozone generator. The gaseous ozone concentration was 50ppm and was continuously introduced into the sodium oxalate solution. Water samples were taken within a certain period of time, immediately passed through a membrane, and then a quencher Na2S2O3 was added to stop the redox reaction in the water sample (quench the residual ozone in the water sample).

[0073] The sodium oxalate content in the water sample was determined by ion chromatography (ICS-600, Thermo Fisher Scientific Inc.), with Na2CO3 / NaHCO3 as the mobile phase and a mobile phase speed of 0.8 mL / min.

[0074] The specific surface area S of the composite active aluminum-based ozone oxidation catalyst prepared in the above examples and comparative examples is BET , carbon content, copper content and the degradation rate of sodium oxalate in the water sample after 25 minutes of catalysis (degradation rate = (C0-C) / C0×100%, where C0 is the initial concentration of sodium oxalate in the water sample, and C is the concentration of sodium oxalate in the water sample after 25 minutes of catalysis) are shown in Table 1 below:

[0075] Table 1

[0076]

[0077] From Table 1 and Figure 6 It can be seen that after 25 minutes of catalytic degradation of a water sample containing sodium oxalate using the catalyst prepared in Example 1, the concentration of sodium oxalate in the water sample was only 3.67% of the initial concentration, while the concentration of sodium oxalate in the water sample treated with the commercial catalyst CuO / γ-Al2O3 was 43.26% of the initial concentration. It can be seen that the catalytic effect of the composite active aluminum-based ozone oxidation catalyst prepared in Example 1 is far better than that of the commercial catalyst (4wt% CuO / γ-Al2O3).

[0078] It can be seen from Example 1 and Comparative Examples 1 and 2 that the carbon contents of the three catalysts prepared in Example 1 and Comparative Examples 1 and 2 are similar, but the types of aluminum-based carriers are different. Among them, the catalyst prepared in Example 1 that only contains an aluminum-based carrier with a β-Al2O3 configuration has the smallest specific surface area, and the carbon content and copper content are relatively the lowest, but its catalytic effect is the best. After 25 minutes of catalytic degradation, the degradation rate can be as high as 96.33%. It can be seen that compared with the catalysts prepared with γ-Al2O3 and Al(OH)3 as aluminum-based carriers, the catalysts with an aluminum-based carrier with a β-Al2O3 configuration have better catalytic activity. In addition, the present invention uses a Thermo Fisher ESCALAB250Xi spectrometer to analyze the metal valence content of the catalysts prepared in Example 1 and Comparative Example 1, and the results are as follows: Figure 7 As shown, compared with Comparative Example 1, the copper element in the catalyst prepared in Example 1 is more in the form of Cu 0 / + It is speculated that the aluminum source ammonium aluminum sulfate used in Example 1 releases ammonia during the pyrolysis process, which can remove part of the Cu 2+ Converted to Cu 0 / + , thus more Cu + As an active site, it donates electrons to ozone, catalytically promoting the decomposition of ozone to produce active free radicals. Therefore, the catalyst prepared in Example 1 exhibits better catalytic activity.

[0079] In addition, the catalyst prepared in Comparative Example 2 and the commercial catalyst CuO / γ-Al2O3 show similarities in aluminum-based carrier configuration and copper content. However, there are two main differences between the two: first, the catalyst prepared in Comparative Example 2 contains a small amount of residual carbon (0.19wt%), while the commercial catalyst does not; second, the specific surface area of ​​the commercial catalyst is higher than that of the catalyst prepared in Comparative Example 2. Although the commercial catalyst has an advantage in specific surface area, the catalytic effect of the catalyst prepared in Comparative Example 2 is far superior to that of the commercial catalyst. This comparison result clearly shows that the introduction of residual carbon significantly improves the catalytic effect of the catalyst to a certain extent, and even exceeds the effect of specific surface area on catalytic performance to a certain extent.

[0080] In summary, the present invention obtains a composite active aluminum-based ozone oxidation catalyst by adopting an aluminum-based carrier with a specific configuration (β-Al2O3) to load transition metals and introducing residual carbon. Under the synergistic effect of the aluminum-based carrier with a specific configuration and the residual carbon, the catalyst exhibits excellent catalytic activity under conditions of lower transition metal element content.

[0081] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.

Claims

1. A composite active aluminum-based ozone oxidation catalyst, characterized in that: The composite active aluminum-based ozone oxidation catalyst comprises an aluminum-based carrier and transition metal elements and carbon supported on the aluminum-based carrier, wherein: The aluminum-based carrier is an aluminum-based carrier with a β-Al2O3 configuration; The transition metal element comprises one or more of Fe, Cu, Mo, Mn and Co; The mass percentage of carbon in the composite active aluminum-based ozone oxidation catalyst is 0.1wt%-1wt%.

2. A composite active aluminum-based ozone oxidation catalyst according to claim 1, characterized in that: The aluminum-based carrier is K-type β-Al2O3 and / or Na-type β-Al2O3; The mass percentage of transition metal elements in the composite active aluminum-based ozone oxidation catalyst is 1wt%-4wt%; The specific surface area of ​​the composite active aluminum-based ozone oxidation catalyst is 4-20m 2 / g.

3. A composite active aluminum-based ozone oxidation catalyst according to claim 1, characterized in that: The composite active aluminum-based ozone oxidation catalyst further comprises nitrogen supported on the aluminum-based carrier; the mass percentage of nitrogen in the composite active aluminum-based ozone oxidation catalyst is 0-0.5wt%.

4. A method for preparing the composite active aluminum-based ozone oxidation catalyst according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) dissolving an aluminum source, a transition metal source, a carbon source and a salt template in water to obtain a uniformly mixed precursor solution; the salt template is a potassium salt and / or a sodium salt; and the aluminum source is ammonium aluminum sulfate; (2) spray drying the precursor solution prepared in step (1) to obtain microsphere powder, and then calcining the microsphere powder to obtain the composite active aluminum-based ozone oxidation catalyst; the calcination temperature is 600-800° C., and the calcination time is 1-4 hours.

5. The preparation method according to claim 4, characterized in that: In step (1), The transition metal source includes a copper source, and the copper source is copper nitrate and / or its hydrate; The carbon source is selected from one or more of glucosamine and its salts, glycine, glucose and sucrose; The salt template is potassium chloride and / or sodium chloride.

6. The preparation method according to claim 4, characterized in that: In step (1), the total solid content of the precursor solution is 6wt%-14wt%; The mass ratio of the aluminum source to the salt template is 1:(1-6).

7. The preparation method according to claim 4, characterized in that: In step (2), during the spray drying process: the pressure is 0.1-0.5 kg / cm 2 , the working vibration frequency of the atomizer is 5-15kHz, the amplitude is 10-20Vpp, the hot air flow rate is 250-350L / min, and the tower top temperature is 150-200℃; The particle size of the microsphere powder is 80-90 μm.

8. The preparation method according to claim 4, characterized in that: The method also includes the steps of washing and drying the calcined product.

9. Use of the composite active aluminum-based ozone oxidation catalyst according to any one of claims 1 to 3 or the composite active aluminum-based ozone oxidation catalyst prepared by the preparation method according to any one of claims 4 to 8 in wastewater treatment.